Socioeconomic status and the relationship of physical performance with activities of daily living among US older adults - Grace Chang; Rahul Malhotra; Benjamin Seligman (PLoS ONE, 2026)
Background Independence in activities of daily living (ADLs) is an important health outcome for older adults and a predictor of morbidity and mortality. Physical performance is closely associated with ADL independence. It is not clear if socioeconomic status (SES) may alter this relationship so that people with more resources may remain independent at lower performance. Objective To assess whether SES is an effect modifier of the association between physical performance and ADL limitations. Methods Using data from the Health and Retirement Study, we considered two outcomes in logistic regression models: cross-sectional presence of ADL limitations and longitudinal development of new limitations. We separately considered two performance measures, gait speed (gait) and grip strength (grip), and three SES measures, education, income, and wealth, with and without an interaction term, for a total of 12 regressions. Covariates were age, sex, comorbidity count, cognition, and BMI (for grip) or height (for gait). Results Respective sample sizes for gait and grip were 4,825 and 3,401 in cross-sectional analysis and 3,995 and 2,860 longitudinally. They were 57–59% female with median ages 69.0–75.4 years. In regressions without interaction terms, gait and grip were significantly associated with greater odds for the presence or development of ADL limitations (0.95 and 0.97 respectively for grip, 0.03 and 0.20 for gait) while SES measures were not. When interaction terms were included, none reached statistical significance. Conclusions We found that SES did not modify the relationship between performance measures and ADL limitations cross-sectionally or longitudinally. Greater SES may not reduce the effort needed for ADLs, or Americans with low SES may similarly access adaptive equipment. Maintaining physical performance remains key for maintaining independence.